1968
DOI: 10.1029/jb073i006p02069
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anomalies in the Pacific and sea floor spreading

Abstract: The symmetric linear magnetic pattern found over the crest of the Pacific‐Antarctic and Juan de Fuca ridges can now be traced across the flanks and into the basins in the North and the South Pacific Ocean. The bilateral symmetry is best shown in the South Pacific, where the western half of the pattern can be traced to the edge of the New Zealand plateau. The eastern half extends to at least 90°W at 62°S. Although sections of the pattern south of the ridge axis have not yet been mapped because of the difficulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

1972
1972
2013
2013

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(49 citation statements)
references
References 44 publications
0
48
0
1
Order By: Relevance
“…The data on which this study is based are given in Pitman et al [1968] and also in Heirtzler [1968]. Le Pichon [1968] has also investigated this region and has found a pole position practically identical to that listed above.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The data on which this study is based are given in Pitman et al [1968] and also in Heirtzler [1968]. Le Pichon [1968] has also investigated this region and has found a pole position practically identical to that listed above.…”
Section: Introductionmentioning
confidence: 95%
“…Magnetic profiles of twelve crossings of this ridge have been presented by Heirtzler [1968] an'd Pitman et al [1968]. Ten of these profiles were analyzed in the following manner to obtain the spreading rates shown in Figure 16 No attempt was made to construct a diagram predicting the spreading rate perpendicular to the strike of the ridge as was done for the Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…Pitman et al (1968) suggested that the magnetic properties of rocks of the Cretaceous quiet zone may have changed owing to diagenetic processes, a scenario that can easily be extended to include the Jurassic Quiet Zone. Indeed, the process of hydrothermal alteration of source basalts has been implied by several authors as a possible cause for the Jurassic Quiet Zone (Vogt et al, 1971;Taylor et al, 1968).…”
Section: The Jurassic Quiet Zonementioning
confidence: 99%
“…Magnetometers towed across the east Pacific (Pitman et al 1968) revealed magnetic stripes that supported a controversial theory of "sea floor spreading", a theory that metamorphosed in 1968 into the all-embracing "theory of plate tectonics" (Morgan 1968). For the first time there was a concept that made sense of a multitude of disparate geological facts.…”
Section: Journal Of Marine and Freshwater Researchmentioning
confidence: 96%